Distribution of schistosomiasis and soil transmitted helminthiasis in Zimbabwe: towards a national plan of action for control and elimination. - Nicholas Midzi; Takafira Mduluza; Moses J Chimbari; Clement Tshuma; Lincoln Charimari; Gibson Mhlanga; Portia Manangazira; Shungu M Munyati; Isaac Phiri; Susan L Mutambu; Stanley S Midzi; Anastancia Ncube; et al. (Public Library of Science (PLoS), 2014)
Schistosomiasis and STH are among the list of neglected tropical diseases considered for control by the WHO. Although both diseases are endemic in Zimbabwe, no nationwide control interventions have been implemented. For this reason in 2009 the Zimbabwe Ministry of Health and Child Care included the two diseases in the 2009-2013 National Health Strategy highlighting the importance of understanding the distribution and burden of the diseases as a prerequisite for elimination interventions. It is against this background that a national survey was conducted.A countrywide cross-sectional survey was carried out in 280 primary schools in 68 districts between September 2010 and August 2011. Schistosoma haematobium was diagnosed using the urine filtration technique. Schistosoma mansoni and STH (hookworms, Trichuris trichiura, Ascaris lumbricoides) were diagnosed using both the Kato Katz and formol ether concentration techniques.Schistosomiasis was more prevalent country-wide (22.7%) than STH (5.5%). The prevalence of S. haematobium was 18.0% while that of S. mansoni was 7.2%. Hookworms were the most common STH with a prevalence of 3.2% followed by A. lumbricoides and T. trichiura with prevalence of 2.5% and 0.1%, respectively. The prevalence of heavy infection intensity as defined by WHO for any schistosome species was 5.8% (range 0%-18.3% in districts). Only light to moderate infection intensities were observed for STH species. The distribution of schistosomiasis and STH varied significantly between provinces, districts and schools (p<0.001). Overall, the prevalence of co-infection with schistosomiasis and STH was 1.5%. The actual co-endemicity of schistosomiasis and STH was observed in 43 (63.2%) of the 68 districts screened.This study provided comprehensive baseline data on the distribution of schistosomiasis and STH that formed the basis for initiating a national control and elimination programme for these two neglected tropical diseases in Zimbabwe.